Faceshopping [from In Real Love (IRL)]. - Sacks, Erika. (Tufts Archival Research Center, 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: Erika's work questions the world of online personas; how the act of self-commercialization on social media platforms parallels the advertising and marketing of products in a nation under capitalism. More recently, Erika's work puts a spotlight on digital romance and dating apps.